Synthesis of Fe catalyst nanoparticles by solution process towards carbon nanotube growth - Mohd Abid, Mohd Asyadi Azam; Zulkapli, Nor Najihah (Maney Publishing, 2015)
The iron catalyst nanoparticles were prepared on silicon wafers by solution process, which first spins coat the solution of iron (III) nitrate nonahydrate and colloidal solution, and then are heated to obtain the formation of iron nanoparticles. The effects of different spin speed and heat treatment parameters during the solution process were investigated. As a result, the smallest thickness of the Fe catalyst thin films is 78 nm, and the smallest Fe catalyst nanoparticles, i.e. 9.67 nm, were obtained at the highest spin speed of 8000 rev min-1 and 500oC. The uniformity of the thin films was also found to increase with increasing spin speed. The particle and thickness analysis was performed by means of field emission scanning electron microscopy.